Exu e Ogum no terreiro de samba: um estudo sobre a religiosidade da escola de samba Vai-Vai - Alexandre, Claudia Regina (2017)
The present research contemplates a study about the complex relationship between the Escola de Samba Vai-Vai, in São Paulo, and some Candomblé religious practices. The narrative is based on a religious confession, which mixes carnival symbology and religion within the samba terreiro. The profane and the sacred cults, which are practiced, mark the group's daily life in a peculiar way and problematize the questions of this research, which aims to understand how expressions of the Afro-Brazilian religions remain in its cultural manifestations; how it was possible to insert the Afro-religious practices in the carnival association´s routine; and how a religious calendar with the worshiping of two Orixás, Exu and Ogum, remains in the samba terreiro. The study begins with the collection of black bodies´ expressions in the colonial period, using concepts such as resistance by the sacred, cultural continuum, ethnic-racial identity and religious syncretism. These are important to understand what occurs in the black territory of the Escola de Samba Vai-Vai, which promotes its religious festivals with a Procession and Ogum´s Feijoada like others candomblé terreiros